Caribbean realism as a garciamarquiana imaginal construction (Encuentros, 2021)
With no intention of continuing to coin labels for the work of Gabriel García Márquez, who every day fights against literary forceps to survive in the face of a growing avalanche of plot proposals, in his attempts to petrify an elusive narrative universe that at every moment she manages to change her skin to assume renewed categorizations sustained by a symbolic autonomy of astonishing peculiarity. In this regard, the theses of symbolic realism are assumed as an instrument to interrogate the work of the Colombian nobel from an imaginal grammar never diminished by the perpetuity of the criteria, but diversified with the acts of reading that are forever functional as processes of subjectivation. From this act of interrogation: one of the answers obtained is Caribbean realism as a possibility to make visible the construction of an imaginal reality that usually represents in the same scenario: the aforementioned event, the actantial etiology and the paradoxes of certainty; all of them wrapped by host symbols that have become a telluric memory, deeply rooted with an existential dialectism, which makes it fluctuate between signifying complicity and creative argumentation.
Keywords: With no intention of continuing to coin labels for the work of Gabriel García Márquez, who every day fights against literary forceps to survive in the face of a growing avalanche of plot proposals, in his attempts to petrify an elusive narrative universe that at every moment she manages to change her skin to assume renewed categorizations sustained by a symbolic autonomy of astonishing peculiarity. In this regard, the theses of symbolic realism are assumed as an instrument to interrogate the work of the Colombian nobel from an imaginal grammar never diminished by the perpetuity of the criteria, but diversified with the acts of reading that are forever functional as processes of subjectivation. From this act of interrogation: one of the answers obtained is Caribbean realism as a possibility to make visible the construction of an imaginal reality that usually represents in the same scenario: the aforementioned event, the actantial etiology and the paradoxes of certainty; all of them wrapped by host symbols that have become a telluric memory, deeply rooted with an existential dialectism, which makes it fluctuate between signifying complicity and creative argumentation.